Trainer Kit Pneumatik sebagai Media Pembelajaran pada Mata Kuliah Mekatronika di Program Studi Pendidikan Vokasional Teknik Elektro Untirta - Prapaskah, Yohanes Aldi; Permata, Endi; Fatkhurrokhman, Mohammad (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2020)
The research is a research and development (R&D) with the aim to produce learning media products in the form of pneumatic trainer kits and pneumatic jobsheet trainers as pneumatic material in mechatronics courses to determine the level of eligibility and strengthening of competencies in Vocational Education in Electrical Engineering FKIP Untirta. This study uses the 4D or Defne model, namely the problem definition stage to be investigated, Design which is the product design stage and the material design josbheet material, Development (Development), namely the product manufacturing stage, product validation as well as user testing with competency strengthening and Dessiminate. The final product resulting from this development research is in the form of an electropneatic trainer kit and jobsheet which is also the main object of research. The method used in collecting data in this study includes interviews, observation, questionnaires and test questions for strengthening psychomotor competence. Testing the feasibility level of pneumatic media trainer kit involves three media experts and three material experts, as well as testing for psychomotor competency strengthening conducted by students of the Electrical Engineering Vocational Education study program in the 6th semester of 2017. The power analysis technique uses quantitative descriptive analysis. Based on the results of the study obtained a score on the feasibility test of media experts to get 91.3 included in the category of